Artificial Intelligence as a Testing Ground for Key Theological Questions - Dorobantu, Marius (Zygon, 2022)
Engagement with artificial intelligence (AI) can be highly beneficial for theology. This article maps the landscape of the various ways such engagement can occur. It begins by outlining the opportunities and limitations of computational theology before diving into speculative territory by imagining how robot theologians might think of divine revelation. The topic of AI and imago Dei is then reviewed, illustrating several ways AI can inform theological anthropology. The article concludes with a more speculative take on the possible implications of AI for divine infinity, incarnation, theodicy, and demonic intelligence.